KEANTONIMAN ADJEKTIVA DALAM BAHASA KAILI - Deni Karsana (Multilingual, 2013)
Semantics is a field of linguistics dealing with the meaning. Field of semantic meaning to be very broad scope. One is antonym. Antonym study is part of the semantic field in particular for the study of lexical meaning. Antonym found in every language. This paper examines how the relationship type meaning antonym in Kaili language. This research uses descriptive qualitative method. The results showed Kaili language antonyms on the word class adjective that can be divided into threetypes, namely bipolar adjective antonyms, balanced antonyms adjective and overlap antonymsadjective.